PENERAPAN TEKNIK RELAKSASI NAFAS DALAM MENURUNKAN INTENSITAS NYERI PADA PASIEN APPENDICITIS DI RSUD WATES - Wahyu Widodo, Neli Qoniah (Jurnal Ilmiah Keperawatan, 2020)
Appendicitis is a condition in which an infection occur in the appendix. In mild cases it can be cured without treatment, but many cases require a laparotomy by removing the tufts of infected worms (Kowalak, 2011). Objective : to determine the effect of deep breathing relaxation with acute pain nursing problems in appendicitis clients. Method : The design of this research is descriptive, in the form of case studies.The subjects in this study were two clients who had appendicitis. The study was conducted in February - March 2019. Results : before taking breath relaxation measures on the scale of pain 6 and 5, after the pain scale measures were carried out to 3 and 2. The results showed a decrease in the scale of moderate pain to a mild pain scale. Conclusion : Breath relaxation techniques can reduce pain intensity in appendicitis patients, So this nonpharmacological technique is highly recommended.